FAKTOR PENDORONG ALIRAN MASUK INVESTASI LANGSUNG ASING DI NEGARA SEDANG BERKEMBANG - Agung Nusantara (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2013)
Foreign Direct Investment flows to developing countries surged in the 1990s, to become their leading source of external financing. This raises in FDI volume make government must be generate domestic policies to push FDI inflows. The first step is identification macroeconomic determinants of FDI inflows.Globerman and Shapiro (2005) suggest the macroecomic variables, such as, market size, resources, and financial sector, may be associated with FDI inflows, especially in developingcountries. The problem is how far the macroeconomic variable can push FDI inflows, in condition, imperfect economic liberalisation.This study proofs that market size, included, domestic economy (GDP) and extention of domestic economy (Openness) significantly push FDI inflow. But debt variable, despite of associated with government policy, significantly impeded FDI inflows.Key words: Foreign Direct Investment, Market Size, and Financial Sector.